KEPEMIMPINAN KEPALA DESA DAN EKSISTENSI BUDAYA GOTONG ROYONG PADA MASYARAKAT PEDESAAN DI INDONESIA - Herdiana, Edy (LPPM UNSAP & FISIP UNSAP, 2024)
The leadership of a village head in the village is expected to contribute to development in accordance with the aspirations of the village community. Through good leadership from a village head in order to provide protection to the community and preserve the noble culture of the community such as the culture of gotong royong. Along with the times and social changes and cultural changes, in a characteristic of rural communities, namely the nature of mutual cooperation needs good attention, especially through the preservation of this culture so that it is not lost with social changes and cultural changes that increasingly come from outside so that sometimes it can eliminate the identity of the cultural personality of the local community. Gotong royong means working together to achieve a desired result. The attitude of gotong royong is to work together in completing work and together enjoy the results of the work fairly.